Evaluasi Kegagalan Penyedia Jasa Konstruksi Dalam Proses Pengadaan Jasa Konstruksi Dengan Sistem Elektronik (Studi Kasus: Dinas Pekerjaan Umum Kabupaten Pelalawan) - Liya Prihatini; Alfian Malik; Ryan Tri Komara (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This study discusses the failure of construction service providers in the procurement of goods / services construction with elektroknik system, competition for winning the auction happens to each contractor who will eventually obtained a contractor is selected as the winner. On the other hand, contractors who follow the auction fails to win the auction, this event certainly detrimental to the contractor. This study aims to determine the variables and the percentage of failure of the failure of the procurement process of construction service providers on government projects particularly in the Public Works Department Kab. Palalawan. The study on procurement of construction services procedures require that the contractor seeks to ways to win the auction. Research data obtained from questionnaires distributed to counterparties contractor and confirmed by interviews of the ULP Party Public Works Department and LPSE Kab. Palalawan. Data processing manually using Microsoft Excel and presented in a bar chart (Bar Chart). Based on these results, the variable most dominant failure of the failure of the procurement process evaluation phase of construction services provider administration in 2012 was (9.1%), the year 2013 was (12.5%), the year 2014 was (16.1 %), the technical evaluation stage of the year 2012 was (9.8%), in 2013 was (8.6%), in 2014 was (15.6%), Stage price evaluation in 2012 was (31.8 %), the year 2013 was (33.3%), in 2014 was (37.5%). Evidence evaluation stage qualification in 2012 was (23.5%), in 2013 was (18.8%), in 2014 was (20.0%).Keyword : Construction, Failure Factors, Electronic Systems (E-procurement), Auction